PENGARUH LEVERAGE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Empiris 16 Perusahaan Sektor Konsumsi yang terdaftar di Bursa Efek Indonesia) - aris (Nusa Putra University, 2021)
The manufacturing industry is showing very promising developments, especially in the aspect of manufacturing value added in the consumer goods sector. Because the products are needed by the wider community. This study aims to analyze how the influence of leverage and profitability on company value, the Food and Beverages Sector Companies listed on the Indonesia Stock Exchange. The research method used is descriptive method and verification method. The sampling technique was carried out using the purposive sampling method, and a sample of 14 Sector Food and Beverages Companies listed on the Indonesia Stock Exchange, in 2015 - 2019. Data analysis used in this study was multiple regression analysis. Statistical test results show that the leverage variable has a relationship with firm value, with a moderate level, while the profitability variable has a very strong relationship with company value. From the results of the research, solvency and profitability have a significant positive effect on firm value. This means that the higher the leverage and profitability, the higher the value of the company. Leverage variables and profitability variables have a significant positive effect on the value of the company, meaning that together the higher the leverage and profitability the higher the value of the company.